O que informam as cartas de leitores e leitoras enviadas a jornais impressos: os casos do Estado de Minas e do Le Monde - Patricia Espirito Santo (2012)
This study analyzes what kind of information is contained in letters sent to printed media by readers of both sexes in the light of Information Sciences with a research line focusing on Information, Culture and Society. It describes the production of newspaper information, especially in sections publishing the readers opinions. In considering communication media information mediators, besides producing andreproducing cultural and social standards, the study attempted to identify what the readers, both male and female, write to newspapers and how they discuss the topics presented on their pages; and whether there would be any differences in the argumentation used by each gender; and also what argumentation the printed media uses in order to draw the attention of their current readers and also their prospect readers; and what the editors, of both genders, deem worth publishing and how theydo it. For that purpose, a conceptual basis was developed of ideas advocated by theorists of Information Sciences, Communication, Discourse Analysis and Gender. Letters spontaneously sent by e-mail to Estado de Minas and Le Monde newspapers were collected during 30 consecutive days and sorted out according to topics and issues. Once those published by the papers had been identified, an analysis of thediscourse was carried out of 60 letters sent Estado de Minas and 92 letters sent to Le Monde, which made it possible to learn the values the readers resort to, on which hierarchy levels they found their values and in which locations they place their argumentation. A comparison was made of the whole contents of 16 original letters to the texts published by the former and of 5 letters by the latter. Results found have led to the conclusion that men sign almost 80% of letters sent to both papers.However, the values, hierarchies and locations presented in the letters of both genders reproduce the ideological and discursive background of each individual person more than they do the gender of the sender. On the other hand, the comparison between the whole contents of letters sent and the texts published in the papers shows that newspapers edit their male and female readers texts by either adding ideas to the orginal texts, as did Estado de Minas, or favoring topics or issues scarcely discussed by the readers, as did Le Monde.